The World Indigenous Research Alliance (WIRA): Mediating and mobilizing Indigenous Peoples' educational knowledge and aspirations - Paul Whitinui; Onowa McIvor; Boni Robertson; Lindsay Morcom; Kimo Cashman; Veronica Arbon (Arizona State University, 2015)
There is an Indigenous resurgence in education occurring globally. For more than a century Euro-western approaches have controlled the provision and quality of education to, and for Indigenous peoples.  The World Indigenous Research Alliance (WIRA) established in 2012, is a grass-roots movement of Indigenous scholars passionate about making a difference for Indigenous peoples and their education. WIRA is a service-oriented endeavor designed by Indigenous scholars working in mainstream institutions to support each other and to provide culturally safe spaces to share ideas. This paper highlights how WIRA came to be, and outlines the nature and scope of these shared endeavours. Strategically, WIRA operates under the mandate of the World Indigenous Nations Higher Educational Consortium (WINHEC) who regularly report to the General Assembly of the United Nations Indigenous Peoples Permanent Forum on Indigenous Issues (UNPFII) pertaining to Indigenous Peoples and their education (United Nations Permanent Forum on Indigenous Issues, 2007). Indeed, this collaboration provides the opportunity to share best practices across respective countries, and to co-design interdisciplinary, dynamic and innovative educational research.  Since the inception of WIRA, a number of research priorities have emerged alongside potential funding models we believe can assist our shared work moving forward.  The launching of WIRA is timely, and sure to accelerate the goals envisaged by WINHEC, and Indigenous peoples aspirations in education more generally.